Håndspålæggelse hos hittitterne - Carstens, Pernille (Religionsvidenskabeligt Tidsskrift, 1995)
By showing Eight Examples of the gesture of hand placement from the religious texts of the hittites, this article discusses the meaning of the rite. The hand placement can be understood as a gesture that qualifies the sacrificial animal. The rite of hand placement is also connected with substitution or elimination rituals. Being a small rite in a large sequence, the hand placement gives rise to a consideration concerning the ritual symmetry in general.